Rapid Development Studio: An Intensive, Iterative Approach to Designing Online Learning. (September 2021) - Mei, Bing; May, Lawrence; Heap, Rena; Ellis, Damon; Tickner, Sue; Thornley, Jacqui; Denton, Jamie; Durham, Richard
Given the increasing demand for online learning at the tertiary level, there currently exists a need to modify or develop instructional design (ID) models/approaches that can effectively facilitate the collaboration between learning designers and teachers, as well as to research the effectiveness of these models/approaches. Against this backdrop, adopting a design-based research approach, we tested a practical ID approach that is developed on two prior models: rapid prototyping and collaborative course development. Accordingly, a 2-week rapid development studio—an agile, intensive, iterative ID process—was arranged. Data from multiple sources were gleaned during the study to generate a comprehensive and in-depth understanding of the proposed approach. Overall, results suggest that the approach is effective for developing online courses in case of a limited time frame and was positively perceived by both course instructors and learning designers. Moreover, practical tips for replicating the process in other contexts are also shared. It is our hope that the study will stimulate further exploration of alternative ID models/approaches to improve online course design efficacy in other higher education institutions.